Imperfection: The Will-to-Control and the Struggle of Letting Go - W. Keith Duffy (Journal of the Assembly for Expanded Perspectives on Learning, 2001)
As I found myself beginning to appropriate my students' writing more and more, I wondered if this was evidence of a spiritual imbalance—an unwillingness to acknowledge my own imperfection as a teacher and human being.